Effect of Dietary Inclusion of Papaya Peel Powder on Serum and Carcass Parameters of Japanese Quails.: - A, Sushma; kallam, Nagaraja kumari; D. Narendra nath; P.Kavitha (Indian Journal of Animal Nutrition, 2023)
The present study was carried out to assess the effect of dietary inclusion of Papaya Peel Powder (PPP) on serum biochemical and carcass parametes of J. quails. Day old Japanese quails (N=150) were distributed randomly to five dietary groups each with three replicates of 10 birds and were maintained under uniform management conditions. Experimental diets were prepared with inclusion of PPP at 0, 1.5, 3.0, 4.5 and 6.0 percent in T1, T2, T3, T4 and T5, respectively and were fed for a period of 0-5 weeks. At the end of the fifth week, blood was collected from two birds per replicate a total of 30 samples for serum analysis. At the end of the trial two birds per replicate were slaughtered and carcass traits were studied. The serum biochemical profile of quails revealed that there was significant increase (P<0.01) in serum total protein, albumin, A/G ratio, HDL-C, calcium and phosphorus with increasing levels of PPP was observed. Whereas, significant decrease (P<0.05) in serum cholesterol and LDL-C was observed from 0 to 6% inclusion of PPP in diet. On the other hand, incorporation of PPP from 0 to 6.0% in the diet had no effect on serum globulin, VLDL-C, triglycerides, SGOT, SGPT, BUN, creatinine and glucose. Carcass traits like pre slaughter live weight, carcass weights and dressing percentage were significantly (P<0.01) increased in PPP supplemented groups (up to 3%) compared to control group. In sensory evaluation of meat, mean scores of colour, juiciness, tenderness and overall acceptability of meat were increased significantly (P<0.01) up to 6.0% PPP inclusion when compared with the other treatment groups. Basing on the results it can be concluded that PPP can be incorporated up to 6.0% level in the diet for the production of designer meat with better organoleptic characters